The transfer and decay of maternal antibodies against enterovirus A71, and dynamics of antibodies due to later natural infections in Chinese infants: a longitudinal, paired mother–neonate cohort study. Issue 3 (March 2021) - Wei, Xianglin; Yang, Juan; Gao, Lidong; Wang, Lili; Liao, Qiaohong; Qiu, Qi; Luo, Kaiwei; Yu, Shuanbao; Zhou, Yonghong; Liu, Fengfeng; Chen, Qi; Zhang, Juanjuan; et al.
Summary: Background: Since 1997, epidemics of hand, foot, and mouth disease associated with enterovirus A71 (EV-A71) have affected children younger than 5 years in the Asia-Pacific region, including mainland China. EV-A71 vaccines have been licensed for use in children aged 6–71 months in China, but not for infants younger than 6 months. We aimed to assess the dynamics of maternal EV-A71 antibodies to inform choice of potential vaccination strategies to protect infants younger than 6 months, because they have a substantial burden of disease. Methods: We did a longitudinal cohort study with mother–neonate pairs in local hospitals in southern China during 2013–18. We collected cord blood from neonates and venous blood from mothers at delivery. We followed up and collected blood samples from the children at ages 2, 4, 6, 12, 24, and 36 months and tested for the presence of neutralising antibodies against EV-A71 with virus neutralisation assays. Seropositivity, or protective titre, was defined as a neutralisation antibody titre of 16 or higher. We estimated the seroprevalence, geometric mean titre (GMT), and transfer ratio of maternal antibodies. We used a binomial distribution to derive the 95% CIs of seroprevalence. Seropositivity between mothers and neonates was compared by use of an agreement (κ), while GMTs were compared by use of paired Student's t tests. Findings: Between Sept 20, 2013, and Oct 14, 2015, 1054 mothers with 1066 neonates were enrolled. The EV-A71 GMT was similar among pairs of neonates (22·7, 95% CI 20·8–24·9) and mothers (22·1, 95% CI 20·2–24·1; p=0·20). The mean transfer ratio of maternal antibodies was 1·03 (95% CI 0·98–1·08). Although 705 (66%) of 1066 neonates acquired protective concentrations of EV-A71 antibodies from mothers, these declined rapidly, with a half-life of 42 days (95% CI 40–44). The time to loss of protective immunity was extended to 5 months in neonates with mothers who had titres of 128 or higher. By age 30 months, 28% of children had become seropositive because of natural infection. Interpretation: EV-A71 maternal antibodies were efficiently transferred to neonates, but declined quickly to below the protective threshold, particularly among those whose mothers had low antibody titres. Our findings suggest that maternal vaccination could be explored to provide neonatal protection against EV-A71 through maternal antibodies. Catch-up vaccination between ages 6 months to 5 years could provide protection to the approximately 30–90% of children that have not had natural EV-A71 infection by that age. Funding: National Science Fund for Distinguished Young Scholars, National Natural Science Foundation of China.